Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

In my logic design exam today I was given this question:

Show that: $$ B \land ( B \lor C) = B $$

It's asking for a proof for this expression. Could someone please explain how such expression can be proven? I'm not that good at Boolean algebra but I believe that it's in the simplest form.

share|cite|improve this question
The question in the title and in the body are different – Dennis Gulko Dec 26 '12 at 9:41
@Dennis Gulko: Thank you, I fixed it. – BSH Dec 26 '12 at 9:43
this is absorption law – Koushik Dec 26 '12 at 9:47
@doniyor that would obviously be wrong, for say $A$ were false but $B$ were true. – peoplepower Dec 26 '12 at 9:51
I think that propositional-logic would be a more appropriate tag than proof-theory. Just have a look at the tag-wiki for propositional-logic and proof-theory. – Martin Sleziak Dec 26 '12 at 9:55

4 Answers 4

up vote 3 down vote accepted

You could simply do it by a truth table. Or use the simple facts that $x\land y$ implies $x$ as well as $x$ implies $x\lor y$. Thus $B\land(\ldots)$ implies $B$ and $B$ implies $B\lor C$ and hence also implies $B\land (B\lor C)$, in summary $B\land(B\lor C)$ and $B$ are equivalent.

share|cite|improve this answer

A truth table will show it

B    C    B or C    B and (B or C)

T    T      T            T
T    F      T            T
F    T      T            F
F    F      F            F 
share|cite|improve this answer
I thought about it but, unfortunately, the teacher said that using truth table isn't acceptable. – BSH Dec 26 '12 at 10:06


Conjunction $x∧y$ behaves on $0$ and $1$ exactly as multiplication does for ordinary algebra: if either $x$ or $y$ is $0$ then $x∧y$ is $0$, but if both are $1$ then $x∧y$ is $1$.

Disjunction $x∨y$ works almost like addition, with $0∨0 = 0$ and $1∨0 = 1$ and $0∨1 = 1$. However there is a difference: $1∨1$ is not $2$ but $1$.

share|cite|improve this answer
∧=* ∨=+ in the above calculation – Koushik Dec 26 '12 at 9:53

Distribute out expression, and you're left with B and B = B or B and C. so that should imply B.

$B \wedge (B \lor C) = (B\wedge B) \lor (B\wedge C )= B \lor (B\wedge C ) = B$

share|cite|improve this answer
Are you sure? The title and body say B∧(B∨C)=B. There is no A. – randomafk Dec 26 '12 at 9:49
Apologies, but I think you might want to. Just look at the URL... /proof-that-b-land-b-lor-c-b – randomafk Dec 26 '12 at 9:51

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.